(untitled) (Journal of the College of Basic Education, 2026)
Dielectric barrier discharges (DBDs) are a typical example of non-thermal atmospheric-pressure gas discharges generated in configurations with an insulating (dielectric) material between the electrodes. This work is to provide a better understanding of the breakdown processes and plasma formation, as well as the effect of the shape and configuration of electrodes on the produced plasma parameters, since the choice of electrode materials, geometry, and arrangement can influence plasma parameters such as electron density, electron energy distribution, and plasma temperature; understanding these characteristics helps optimize the plasma for specific applications. Three types of DBD plasma systems were presented in this work by varying the electrode shape and arrangement; the results indicated that electrode shape and configuration play essential roles in determining plasma parameters